2014
DOI: 10.1016/j.apmr.2014.05.005
|View full text |Cite
|
Sign up to set email alerts
|

What Do We Really Know About the Safety of Tai Chi?: A Systematic Review of Adverse Event Reports in Randomized Trials

Abstract: Objective Systematically review frequency and quality of adverse event (AE) reports in randomized clinical trials (RCTs) of Tai Chi (TC). Data Sources Electronic searches of PubMed/MEDLINE and additional databases from inception through March 2013 of English-language RCTs. Search terms were tai chi, taiji, tai chi chuan. Data were independently extracted by two investigators. Study Selection We included all available randomized controlled trials (RCTs) that were published in English and used Tai Chi as an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
82
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(87 citation statements)
references
References 80 publications
3
82
1
1
Order By: Relevance
“…Increased awareness of posture and breathing improves participants’ ability to anticipate and manage their symptoms, decreasing the risk of precipitating a vicious cycle of breathlessness and anxiety. These modalities have been shown to be safe in patients with chronic heart failure, coronary artery disease (recovering from bypass surgery and myocardial infarction), frailty, arthritis, and vestibular disease 127. These activities can be performed at home, can be done seated, and may be enjoyable alternatives to walking or using exercise equipment.…”
Section: Chronic Obstructive Pulmonary Disease and Pulmonary Rehabilimentioning
confidence: 99%
“…Increased awareness of posture and breathing improves participants’ ability to anticipate and manage their symptoms, decreasing the risk of precipitating a vicious cycle of breathlessness and anxiety. These modalities have been shown to be safe in patients with chronic heart failure, coronary artery disease (recovering from bypass surgery and myocardial infarction), frailty, arthritis, and vestibular disease 127. These activities can be performed at home, can be done seated, and may be enjoyable alternatives to walking or using exercise equipment.…”
Section: Chronic Obstructive Pulmonary Disease and Pulmonary Rehabilimentioning
confidence: 99%
“…Whether traditional Chinese exercise is more beneficial in improving physical function in patients with stroke than other exercise therapy or without intervention is presently vague. A systematic review of adverse event reports in randomized trials [29] has reported certain adverse effects. These effects include muscle problems [30][31][32] and dizziness or hypotension [33].…”
Section: Introductionmentioning
confidence: 99%
“…Tai chi has been shown to be safe in older and deconditioned individuals and in patients with coronary heart disease. (23, 42) No tai chi related side effects have been reported even among high-risk patients (i.e., those recovering from coronary bypass surgery (43) or with heart failure and ejection fraction <40% and NYHA class up to III). (17, 40) The most common adverse effect of tai chi practice is muscle soreness (usually mild and lasting only a few days).…”
Section: Methodsmentioning
confidence: 99%
“…(1820) First, it can be practiced safely by elderly and deconditioned individuals. (2123) Tai chi gentle exercise training may also be more attractive to women, who typically dislike the exercise training offered in CRs. (24) Second, since tai chi practice does not require any particular equipment, it can be practiced at any time and place, thus facilitating adherence.…”
Section: Introductionmentioning
confidence: 99%